Comparison of COVID-19 Infection Among Vaccinated and Unvaccinated Patients in Bangladesh During Second Wave: Single Centre Study (Bangladesh Heart Journal, 2023)
Background: Vaccination may positively influence the clinical outcome of corona virus disease-19 (COVID-19) patients. But there is a lack of data regarding efficacy of vaccine against COVID-19 infection. This study aimed to compare the baseline characteristics, clinical profiles, and outcomes of COVID-19 infection in vaccinated and non-vaccinated patients in Bangladesh in the second wave.Methods: This single centre prospective observational cohort study was carried out at National Heart Foundation Hospital & Research Institute from 27th February 2021 to 25th September, 2021 during the second wave. All COVID-positive patients & cardiac patients who became COVID-19 positive during the period of admission were included in this study for comparison.Results: A total of 858 patients were included. Most patients in the second were unvaccinated (n= 691, 80.5%), while of the 167 individuals who were vaccinated, 125 (14.6%) patients were partially vaccinated while 42 (4.9%) were fully vaccinated. The mean age of the unvaccinated patients was 52.63±16.4 years, partially vaccinated patients was 39.74±14.88 years, and fully vaccinated patients was 50.55 ± 12.48 years (p=0.001). Male were predominant in all groups. In the unvaccinated (98.4% vs 1.6%; p=0.001) and fully vaccinated (81% vs 19%; p=0.001) groups non healthcare personnel (non-HCP) were most commonly affected. Most of the patients (48.7%) in unvaccinated group had ≥4 co-morbidities, while in partially- (51.2%) and fully vaccinated (54.7%) groups most of the patients had